2003
DOI: 10.1007/s00428-003-0854-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and immunohistochemical features of a sebaceous carcinoma arising within a benign dermoid cyst of the ovary

Abstract: Pure sebaceous neoplasms arising in dermoid cysts of the ovary are exceedingly rare. A 63-year-old female with abdominal swelling and pain underwent a right salpingo-oophorectomy that showed a unilocular cyst weighing 830 g and measuring 15x12x10 cm, filled with sebaceous material containing a few hair shafts. The cyst wall exhibited plaques protruding into the cavity of the cyst. Microscopy revealed a dermoid cyst with nests and lobules of atypical and infiltrating sebaceous cells surrounded by basaloid cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…Sebaceous epithelioma and basal cell carcinoma with sebaceousdifferentiationmustbeconsideredinthedifferential diagnosis.Thepresenceofobviousmalignantsebaceousdifferentiationinnearlyeverytumornestandlackofperipheral palisadingandperi-tumoralmyxoidstromaexcludethesediagnoses.Moreover,thelobulatedgrowthpatternwithpushing ratherthaninfiltrativebordersandthematuresebaceouscells dominatingoverbasaloidcellsarehelpfulmorphologicalfeaturesforthediagnosisofasebaceousepithelioma [6][7][8].Since expression of EMA is exceptional in basal cell carcinomas, focalEMAstaining,asinourcase,isusefulindistinguishing sebaceouscarcinomasfrombasalcellcarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sebaceous epithelioma and basal cell carcinoma with sebaceousdifferentiationmustbeconsideredinthedifferential diagnosis.Thepresenceofobviousmalignantsebaceousdifferentiationinnearlyeverytumornestandlackofperipheral palisadingandperi-tumoralmyxoidstromaexcludethesediagnoses.Moreover,thelobulatedgrowthpatternwithpushing ratherthaninfiltrativebordersandthematuresebaceouscells dominatingoverbasaloidcellsarehelpfulmorphologicalfeaturesforthediagnosisofasebaceousepithelioma [6][7][8].Since expression of EMA is exceptional in basal cell carcinomas, focalEMAstaining,asinourcase,isusefulindistinguishing sebaceouscarcinomasfrombasalcellcarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that they originate from pluripotent stem cells, while others suggested that they may originate from more differentiated sebaceous cells in mature teratomas that undergo malignant change rather than from stem cells [8]. Additionally, mutational inactivation of the p53 gene may be involved in the malignant change of sebaceousneoplasmsand,inassociationwithlowproliferativerate (Ki67),mayberelatedtofavorableoutcome [8].Overexpressionofc-erbB-2isfoundin83%ofsebaceouscarcinomas,but isnotassociatedwithanyspecificpathologicalfindingsorclinicaloutcome.Hormonalreceptorsaredetectableinupto22% ofsebaceouscarcinomas,suggestingahormonalinfluenceon these neoplasms [8]. In the present study, c-erbB-2, estrogen andprogesteronereceptorswerenegative,whereasthemitotic indexKi67waspositivefor20%oftheneoplasticcells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations